2017
DOI: 10.4172/2469-9780.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Preventive Effect of Dual-Task and N-Back Task- Incorporated Music Therapy against Dementia

Abstract: Introduction: Alzheimer's dementia (AD) is the most dominant (more than 60%) in the whole dementia and the incidence of AD for people at age 65 years or older becomes twice with an increase in age by 5 years, so the development of countermeasures against it is an urgent issue. For improving cognitive functions, the effectiveness of dual-task (a task for which two different things are performed at the same time) and that of n-back task (a task for which delayed recall of a thing performed at n times ago is carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Through assigning robots with such screening, it becomes easier to monitor the elderly's cognitive function in their home and facilities, allowing for a more systematic approach to dementia prevention. It would thus be ideal if robots can be used to mitigate stress and prevent depression through therapeutic exercises such as dance [5] and brain training [15,16]. Furthermore, we also found that intervention by robots fostered exchanges among participants and created a harmonious atmosphere.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Through assigning robots with such screening, it becomes easier to monitor the elderly's cognitive function in their home and facilities, allowing for a more systematic approach to dementia prevention. It would thus be ideal if robots can be used to mitigate stress and prevent depression through therapeutic exercises such as dance [5] and brain training [15,16]. Furthermore, we also found that intervention by robots fostered exchanges among participants and created a harmonious atmosphere.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, in preliminary testing, we examined delayed playback task and the validity of dual-task [15,16], and developed cognitive dance therapy to add delayed playback task and dual task as part of brain training [5]. If robots are able to perform health-care functions as outlined above, the societal benefits would be enormous.…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic adrenal medullary (SAM) axis is activated by the hypothalamus to stimulate a sympathetic nervous system response, which then stimulates the adrenal medulla to produce epinephrine and norepinephrine ( Antoun et al, 2017 ). The release of norepinephrine is then responsible for the synthesis and release of alpha-amylase ( Sawami et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Robots can be used to mitigate stress [14], deter dementia and depression and aid in therapeutic exercises, thus providing a large benefits to the elderly, their family and health-care providers. Furthermore in preliminary testing, we examined delayed playback task and the validity of dual task [15,16], and developed cognitive-dance therapy to add delayed playback task and dual task as part of brain training [5]. If robots are able to perform health-care functions as outlined above, the societal benefits would be enormous.…”
Section: Introductionmentioning
confidence: 99%